Restoring the endothelial barrier function in the elderly. (June 2021) - Barabutis, Nektarios; Akhter, Mohammad S.; Kubra, Khadeja-Tul; Uddin, Mohammad A.
Highlights: Endothelial Barrier Dysfunction is Associated with Acute Respiratory Distress Syndrome (ARDS). ARDS is associated with high mortality rates in the elderly. Mild Unfolded Protein Response (UPR) activation repairs the endothelium. Activation of UPR may deliver a new therapeutic approach towards ARDS. LPS reduces the activation of the UPR sensor inositol-requiring enzyme-1a in mice lungs. Abstract: Endothelial barrier dysfunction in the elderly has been associated with severe disorders, including acute respiratory distress syndrome, sepsis and COVID-19. Herein we deliver an opinion regarding the development of alternative therapeutic avenues to counteract the pathogenesis of the corresponding diseases.